Resecting orbicularis oculi muscle in upper eyelid blepharoplasty – A review of the literature - Hoorntje, Lidewij E.; Lei, Berend van der; Stollenwerck, Guido A.; Kon, Moshe (Journal of plastic, reconstructive & aesthetic surgery, 2010)
Blepharoplasty of the upper eyelids is one of the most commonly performed procedures in aesthetic plastic surgery. However, the rationale for muscle resection along with skin is uncertain. A PubMed search was performed using the following keywords: ‘blepharoplasty’ and ‘muscle’ as well as ‘blepharoplasty’ and ‘orbicularis’. This yielded 419 different hits. All abstracts from English, Dutch, German or French papers were scanned for potential relevance; of which 59 papers were retrieved. The papers were considered to be relevant for our review if they described their technique for upper blepharoplasty and if they mentioned whether or not they resected orbicularis oculi muscle. Papers describing blepharoplasty combined with other surgical interventions were not included unless specific remarks about the blepharoplasty and the role of orbicularis resection were made. Studies describing a surgical technique specifically designed to create an epicanthal fold in Asians were excluded as well. In total, 55 papers were included for review. Various reasons for muscle resection are described; most authors resect muscle without providing a reason to do so. In more recent literature, a trend towards muscle preservation is observed. A lack of consensus about what is to be done with the orbicularis oculi muscle in upper lid blepharoplasty is demonstrated. This amounts to a shortcoming, especially in training young plastic surgeons. Therefore, an algorithm is proposed.